(untitled) (XXI Century. Spanish Literature and Culture, 2004)
Computational or executive intelligence? Intelligence is a double-edged sword that misused can become stupidity if used in unrelated contexts. Because of this, the author claims the need for a pedagogy that studies stupidity in order to do away with it, since out of a healthy context intelligence can be used as heavy machinery, just as it is done at war, in terrorism, as it was done by the Nazis and in several other examples.